Reconstruction of the Role From the Prosecutor Based on the Socio-Legal Approach - Hamdan Rampadio (Rechtsidee: Law Journal, 2022)
The prosecutor is one of the law enforcement officers who have an orientation to enforce the law in society. The prosecutor in this case does not only apply the law in the form of written texts in the Act, but also looks at the context in social-societal reality. This study aims to explore the socio-legal aspects in implementing the duties of the prosecutor in realizing justice in society. This research is a normative legal research by prioritizing socio-legal aspects. This study uses primary legal materials, namely: the 1945 Constitution of the Republic of Indonesia, the Prosecutor's Law, the Prosecutor's Regulation on Restorative Justice. Secondary legal materials include: books, journal articles, as well as various research results on law enforcement by the Attorney General's Office. Non-legal materials include: various results of non-legal studies on law enforcement by the Attorney General's Office. The approach in this study uses a conceptual approach and a statutory approach. The results of the study confirm that prosecutors in law enforcement in Indonesia are oriented towards law enforcement tasks in the field, which means that prosecutors need to look at non-legal aspects and understand several aspects of social reality in society to maximally enforce the law in society. The urgency of the socio-legal approach regarding the role of prosecutors in Indonesia is to make prosecutors more comprehensive in understanding legal issues that develop in society.